Bromatologia e nutrição do milho submetido à doses de potássio em sistema de integração lavoura-pecuária - Cruz, Simério Carlos da Silva; Bicudo, Silvio José [UNESP]; Machado, Carla Gomes; Pereira, Francisco Rafael da Silva; Brachtvogel, Elizeu Luiz (My University, 2013)
This work aimed at assessing the effect of potassic fertilization on the bromatology and macronutrients content of maize grown in a system integrating agriculture and cattle raising. The experiment was carried out at UNESP, in Botucatu, São Paulo state, during the agricultural season of 2007–8 and 2008–9. It consisted of sixteen treatments in random blocks with parcels being subdivided in four replications. Each K2O dosage (0, 75, 150, and 225 kilos per hectare) corresponded to a parcel, the sub-parcels being made up by the presence or absence of Brachiaria brizantha cv. Marandu grown as mulch. Subsub-parcels were made up of growing systems (maize intercropped or not with Brachiaria brizantha cv. Marandu). One can notice that rates of neutral detergent fiber, acid detergent fiber and of crude protein fitted linear equations, which were negative regarding both neutral detergent fiber and acid detergent fiber; and positive in regard to crude protein. In other words, neutral detergent and acid detergent fibers’ rates reduced dramatically with the increase of K2O dosages per hectare. These results lead to the conclusion that maize plant bromatologic quality improves when it is grown under mulch of Brachiaria brizantha cv. Marandu and treated with increasing K2O dosages. The presence of Brachiaria brizantha cv. Marandu grown as mulch provides higher levels of Mg, N and P in corn grown in succession. The Brachiaria brizantha cv. Marandu when grown in intercropping increased the content of Ca in plant tissue of corn.

Objetivou-se com este trabalho avaliar o efeito da adubação potássica sobre a bromatologia e o teor de macronutrientes na planta de milho cultivado em sistema de integração lavoura-pecuária. O experimento foi conduzido na UNESP, em Botucatu (SP), nos anos agrícolas de 2007/2008 e 2008/2009. O experimento consistiu de 16 tratamentos estabelecidos em esquema de blocos casualisados com parcelas subsubdivididas em quatro repetições. Cada dose de K2O (0, 75, 150, 225 kg ha-1 ) correspondeu a uma parcela, sendo as subparcelas formadas pela presença ou ausência de Brachiaria brizantha cv. Marandu cultivada como planta de cobertura; as subsubparcelas foram compostas por dois sistemas de cultivo (milho solteiro e milho consorciado com Brachiaria brizantha cv. Marandu). Os valores de fibra em detergente neutro, fibra em detergente ácido e proteína bruta se ajustaram a equações lineares, as quais foram negativas para fibra em detergente neutro e fibra em detergente ácido e positivas para proteína bruta; noutros termos, os valores de fibra em detergente neutro e fibra em detergente ácido reduziram significativamente com o aumento das doses em kg ha-1 de K2O. Conclui-se então, que a planta de milho tem sua qualidade bromatológica melhorada quando cultivada sob palhada de Brachiaria brizantha cv. Marandu e submetida a doses crescentes de K2O. A presença de Brachiaria brizantha cv. Marandu como planta de cobertura proporciona maiores teores de Mg, N e P na planta de milho cultivado em sucessão. A Brachiaria brizantha cv. Marandu quando cultivada em consórcio, eleva o teor de Ca no tecido vegetal do milho.
The bromatology and nutrition of maize treated with potassium dosages in a system integrating agriculture and cattle raising
Keywords: Neutral detergent fiber; Acid detergent fiber; Crude protein; K2O levels; Fibra em detergente neutro; Fibra em detergente ácido; Proteína bruta; Níveis de K2O